(untitled) (project baikal, 2020)
The news section presents the UIA Declaration adopted during COP25, the United Nations climate conference meeting; announces the 2020 Kaira Looro Competition, the 2A City-Architecture Movie Awards, as well as this year’s UNESCO-UIA World Capital of Architecture programme in Rio de Janeiro.